Species‐specific fish larvae drift in anthropogenically constructed riparian zones on the Vienna impoundment of the River Danube, Austria: Species occurrence, frequencies, and seasonal patterns based on DNA barcoding. (6th July 2018) - Meulenbroek, Paul; Drexler, Silke; Huemer, Daniela; Gruber, Stephanie; Krumböck, Susanne; Rauch, Pablo; Stauffer, Christian; Waidbacher, Viktoria; Zirgoi, Sabine; Zwettler, Matthias; Waidbacher, Herwig
Abstract: As a result of river regulations over several centuries, followed by restoration measures in recent decades, most of the River Danube shoreline is man‐made, primarily riprap, but some reconstructed gravel banks and riparian side arms. We investigated the effects of these different structures on fish larval dispersal over a 20‐km stretch in Vienna via the use of drift nets. The habitats examined were created 18 years ago when the impoundment of the Danube hydropower station Vienna/Freudenau was constructed. About 15, 000 fish larvae were trapped, and a subsample was determined to species level by DNA barcoding. In total, 26 different species were detected, including 10 species that are endangered or in danger of extinction. When species composition was considered, cyprinids become dominant at sites downstream of gravel bars, whereas in riprap sections, the majority of the larvae consist of invasive Gobiidae. Side arm habitats provide spawning and nursery grounds for additional species. Furthermore, clear species‐related seasonal patterns were observed with peak densities and multiple spawning periods of some species being recorded. The largest peak of Percidae occurred in the first half of May, followed by Cyprinidae at the end of May and Gobiidae in mid‐June.